Motivation and Engagement in Extensive Reading: Insights from EFL Learners at a Science University - Akihiro Saito (IAFOR Journal of Education)
Extensive Reading (ER) is widely recognized as an effective method for improving language proficiency and fostering reading motivation in English as a foreign language contexts. However, the success of ER programs depends on several factors, including student motivation, engagement, and preferences for book selection. This study examines the characteristics of motivation and engagement in an ER program implemented at a science university. Using a mixed-methods approach, the study analyzes quantitative data from the MReader platform, such as total words read, quiz performance, and engagement levels. Further, it draws on a qualitative survey on students’ preferences for books and their motivations for reading. Group comparisons based on a 100,000-word reading threshold suggest that higher engagement correlates with greater gains in proficiency. A stepwise regression analysis identifies key predictors for improvement in reading proficiency. Content analysis reveals that personal interest, familiarity with the material, and perceived learning value significantly influence book selection. Furthermore, motivations for continuing to read are driven by intrinsic enjoyment, the desire for knowledge acquisition, and the academic benefits associated with reading. Meanwhile, obstacles such as reading fatigue, difficulty of the material, and lack of interest can hinder engagement. The study highlights the importance of providing diverse and engaging reading materials, as well as structured goal-setting strategies, to enhance participation in ER programs. These insights contribute to the optimization of ER initiatives, particularly in science-focused settings.